Doing Business in the European Union 2020 : Ireland - World Bank Group (World Bank, Washington, DC, 2020)
Doing Business was the first global indicator created to measure aspects of regulation that enable or hinder the owners of small and medium-size businesses in starting, operating or expanding their companies. In its annual publication, each economy is represented by its largest business city and compared globally with another one hundred and eighty-seven economies. Doing Business in the European Union 2020 Ireland benchmark twenty-four additional cities, capturing regional differences in regulations and their enforcement. This report aims to fill some of the gaps in what is known about the quality and features of business regulations in Ireland by creating regional level data that can be used to analyze the regulatory hurdles entrepreneurs face in five main cities of Cork, Dublin, Galway, Limerick and Waterford. The report also lists recommendations for reforms and good practices in each of the five areas measured that Irish cities can adopt to allow businesses to operate more effectively.